Targeting Homogentisate Dioxygenase Dysfunction in Alkaptonuria: Investigating Curcuma longa’s Therapeutic Potential - Anuradha N. Gangapur (International Journal of Biochemistry and Biomolecule Research, 2024)
Objectives: Alkaptonuria is known to have a faulty gene HGO in the metabolic process. In the present research work, the focus is towards investigating the therapeutic capabilities of the Curcuma longa upon the faulty Homogentisate dioxygenase gene using ligand-protein binding, which would assist in the corrective tyrosine metabolism. Methods: This study is based on the computational approach using different phytochemicals for evaluation of the potency against the abnormal Homogentisate dioxygenase gene. The database of protein PDB databank was used for the protein retrieval. The structural evaluation on the secondary aspect was considered and ligand with suitable pursuit was done to visualise their binding on two dimensions by performing molecular docking using Pyrx and visualization through the BIOVIA discovery studio. Results: The Docking results of the Ligand and protein reported that the selected phytochemical compounds of Curcuma longa have a potential binding affinity with the Homogentisate dioxygenase ligand. The resultant docking previewed to have two compounds to have a high binding affinity with (-7.2) both, which proposes to have good efficacy of the drug. Conclusion: The selected compounds in the present research work that is Curcuma longa exhibit to have better efficacy of drug in treating the faulty gene in the tyrosine metabolism in Alakptonuria by revealing high binding affinity.
Keywords: Alkaptonuria; Curcuma longa; binding affinity; faulty metabolic gene; homogentisate Dioxygenase; molecular docking; phytochemical compounds